Hydrodynamic Investigation on Deep Desulfurization of Liquid Fuel at the Microscale. Issue 10 (28th July 2020) - Al-Azzawi, Marwah; Husain, Afzal; Mjalli, Farouk S.; Al-Wahaibi, Talal; Al-Hashmi, Abdulaziz; Abu-Jdayil, Basim
Abstract: Microscale processes offer a substantial advantage to the process industry as separation is conducted rapidly and efficiently. However, the effectiveness of the separation depends on the stability of the flow regime. Experimental and numerical analysis was carried out to characterize the flow patterns of polyethylene glycol 200 (PEG200) and diesel fuel at several flow ratios in order to achieve optimal conditions for a stable pattern. Computational fluid dynamics (CFD) was employed using the volume‐of‐fluid (VOF) model and the results were validated with the experimental data. Both experimental and numerical outcomes revealed two‐phase flow patterns. These findings enable the application of the simulated module for further liquid‐liquid mass transfer studies where sulfuric compounds exist as solutes in the fuel. Abstract : The efficiency of a liquid‐liquid microchannel device is significantly influenced by the flow patterns. The occurrence of different flow regimes in microchannels depends strongly on various parameters, which were investigated experimentally and numerically. Reaching a good agreement between both procedures can solve many issues and enhance the development of the microprocess considerably.